2021
DOI: 10.1111/srt.13080
|View full text |Cite
|
Sign up to set email alerts
|

In elderly Caucasian women, younger facial perceived age correlates with better forearm skin microcirculation reactivity

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Between the ages of 20 and 70 years, the microcirculation of skin is reduced by 40% in an aging patient. 46 The microcirculation is diminished, resulting in skin changes such as decreased epidermal and dermal thicknesses and composition, as well as flattening of the dermal–epidermal junction. In vitro experiments revealed that Ly could not only improve the energy metabolism of PRSF cells but also increase the VEGF protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between the ages of 20 and 70 years, the microcirculation of skin is reduced by 40% in an aging patient. 46 The microcirculation is diminished, resulting in skin changes such as decreased epidermal and dermal thicknesses and composition, as well as flattening of the dermal–epidermal junction. In vitro experiments revealed that Ly could not only improve the energy metabolism of PRSF cells but also increase the VEGF protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Between the ages of 20 and 70 years, the microcirculation of skin is reduced by 40% in an aging patient. 46 The microcirculation is diminished, resulting in skin changes such as decreased epidermal and dermal thicknesses and composition, as well as flattening of the dermal-epidermal junction.…”
Section: Discussionmentioning
confidence: 99%